Novel function for the p38-MK2 signaling pathway in circulating CD1c+ (BDCA-1+) myeloid dendritic cells from healthy donors and advanced cancer patients; inhibition of p38 enhances IL-12 whilst suppressing IL-10 - Franks, Hester A.; Wang, Qunwei; Lax, Stephanie J.; Colllins, Mary K.; Escors, David; Patel, Poulam M.; Jackson, Andrew M. (Wiley, 2014)
There is growing interest in myeloid (my) dendritic cells (DC) as an alternative to monocyte-derived DC (moDC) for immunotherapy. However, in contrast to moDC, little is known regarding the effect of malignancy on the function, abundance or use of intracellular signaling pathways in myDC. Understanding the molecular detail of circulating myDC is therefore important for future use in advanced cancer. Advanced cancer patients had similar numbers of circulating myDC to cancer-free patients and healthy individuals, and secreted similar levels of IL-1β, IL-6, IL-10, IL-12 and IL-23. However, myDC from some patients failed to secrete the Th1-cytokine IL-12. Surprisingly, inhibiting p38 (p38i) signaling (using BIRB0796 or SB203580) markedly increased IL-12 secretion by myDC. This is in complete contrast to what is established for moDC where inhibiting p38 ablates IL-12. Interestingly, this was specific to IL-12, since IL-10 was suppressed by p38i in both DC types. The opposing effect of p38i on IL-12 was evident at the transcriptional level and in both DC types was mediated through the p38-MK2 pathway but did not involve differential phosphorylation of the distal Rsk kinase. Importantly, where patient myDC did not secrete IL-12 (or after treatment with suppressive melanoma lysate), p38i restored IL-12 to normal levels. In contrast to p38, inhibiting the other MAPK pathways had similar consequences in both DC types. We show for the first time the differential use of a major intracellular signaling pathway by myDC. Importantly, there are sufficient circulating myDC in advanced cancer patients to consider development of adoptive immunotherapy.